2017
DOI: 10.1021/acs.energyfuels.7b01611
|View full text |Cite
|
Sign up to set email alerts
|

Air-Blown Entrained Flow Gasification of Biocoal: Gasification Kinetics and Char Behavior

Abstract: Air-blown entrained flow gasification of biomass has the potential of overcoming tar-related problems that occur in fixed bed or fluidized bed gasifiers. For designing entrained flow reactors (EFR), specific information on the gasification behavior of the fuel is required. Therefore, experiments with biocoal from the hydrothermal carbonization of different feedstock (beech, biogenic residuals, municipal waste, and green waste) are performed under EFR conditions and compared to lignite. Pyrolysis chars from bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…As an efficient and clean coal conversion technology, low-rank coal gasification has attracted increasing attention. It is widely used in many fields such as chemical synthesis and gas production. Entrained flow gasification is considered as the most advanced gasification technology due to its flexible adaptability of gasification feedstock. Its typical feature is the formation of liquid slag . The ash phase was changed due to the ash melting under such a high temperature, and consequently, it influenced the gasification reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…As an efficient and clean coal conversion technology, low-rank coal gasification has attracted increasing attention. It is widely used in many fields such as chemical synthesis and gas production. Entrained flow gasification is considered as the most advanced gasification technology due to its flexible adaptability of gasification feedstock. Its typical feature is the formation of liquid slag . The ash phase was changed due to the ash melting under such a high temperature, and consequently, it influenced the gasification reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis gas is the main material for producing chemicals and fuels for integrated gasification combined cycle (IGCC) power generation . Entrained-flow gasifier is operated with slag tap; thus, the transition of char slag not only affects the carbon conversion but the flow properties of molten slag. , While the carbon conversion efficiencies of gasifiers for high-ash-content coals are distinctly decreased, the residual carbon in slag is high . This demonstrated that, at high operating temperatures, the inorganic melt phase engulfs the organic portion, rendering the organic component unreactive.…”
Section: Introductionmentioning
confidence: 99%